2012
DOI: 10.1186/1756-3305-5-73
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic action of imidacloprid and flumethrin and their release kinetics from collars applied for ectoparasite control in dogs and cats

Abstract: BackgroundThe control of tick and flea burdens in dogs and cats has become essential to the control of important and emerging vector borne diseases, some of which are zoonoses. Flea worry and flea bite hypersensitivity are additionally a significant disease entity in dogs and cats. Owner compliance in maintaining the pressure of control measures has been shown to be poor. For these reasons efforts are continuously being made to develop ectoparasiticides and application methods that are safe, effective and easy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…Some of these studies have also presented data demonstrating a repellency effect, employing various protocols. Stanneck et al (2012a) demonstrated the acaricidal efficacy of Seresto ® (100 % for 8 months duration) against the Brown dog tick Rhipicephalus sanguineus after 24 h incubation with hair from treated dogs and cats. Efficacy and repellency against several tick species were shown by Stanneck et al (2012b).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some of these studies have also presented data demonstrating a repellency effect, employing various protocols. Stanneck et al (2012a) demonstrated the acaricidal efficacy of Seresto ® (100 % for 8 months duration) against the Brown dog tick Rhipicephalus sanguineus after 24 h incubation with hair from treated dogs and cats. Efficacy and repellency against several tick species were shown by Stanneck et al (2012b).…”
Section: Discussionmentioning
confidence: 95%
“…The Seresto ® collar (Bayer, 10 % imidacloprid, 4.5 % flumethrin), is a polymer matrix collar for dogs and cats that allows a continuous and prolonged release of the active ingredients imidacloprid, a chloronicotinyl compound, and flumethrin, an α-cyanopyrethroid, onto the skin surface and hair coat of treated animals (Stanneck et al 2012a). It has been shown to achieve long-term persistent efficacy of 8 months against fleas (Ctenocephalides felis felis) (Stanneck et al 2012b(Stanneck et al , 2012c) and 4 months against I. holocyclus on dogs (Smith et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Failure to apply an ectoparasiticide correctly jeopardises the entire strategy [77]. Breakdown in ectoparasite control programs are thought to occur frequently, and poor owner compliance is an important reason for this [78]. Use of the incorrect frequency of application or dose of the product through misunderstanding or oversight is common, risking ectoparasite attachment, feeding and pathogen transmission [78].…”
Section: Paradigm 5: Prevention Is Better Than Curementioning
confidence: 99%
“…Breakdown in ectoparasite control programs are thought to occur frequently, and poor owner compliance is an important reason for this [78]. Use of the incorrect frequency of application or dose of the product through misunderstanding or oversight is common, risking ectoparasite attachment, feeding and pathogen transmission [78]. Application of the product by the wrong route, such as inadvertent oral administration of a spot-on product has been recorded [79].…”
Section: Paradigm 5: Prevention Is Better Than Curementioning
confidence: 99%
“…Currently available options for the control of I. holocyclus on dogs are limited and include topically applied spot-ons or sprays containing permethrin or fipronil that require fortnightly reapplication, or collars containing flumethrin, amitraz or deltamethrin that give protection for 6 weeks to 3 months. Seresto ® (Bayer; Investigational Veterinary Product (IVP)) contains imidacloprid (10 %), an insecticide from the chloronicotinyl group of compounds, and flumethrin (4.5 %), an ectoparasiticide belonging to the α-cyano-pyrethroids, in a novel polymer matrix collar that allows for their slow and continuous release onto the skin surface and hair coat of a treated animal (Stanneck et al 2012a). The IVP is registered for use on dogs and cats in many countries including in the European Union, the United Kingdom, the United States of America and New Zealand.…”
Section: Introductionmentioning
confidence: 99%